Hotspot Mutations in SARS-CoV-2 - Saha, Indrajit; Ghosh, Nimisha; Sharma , Nikhil; Nandi, Suman (Frontiers in Genetics, 2021)
Since its emergence in Wuhan, China, SARS-CoV-2 has spread very rapidly around the world resulting in a global pandemic. Though the vaccination process has started, the number of COVID affected patients is still quite large. Hence, the analysis of hotspot mutations of the different evolving virus strains needs to be carried out. In this regard, multiple sequence alignment of 71038 SARS-CoV-2 genomes of 98 countries over the period from January 2020 to June 2021 is performed using MAFFT followed by phylogenetic analysis in order to visualise the virus evolution. These steps resulted in the identification of hotspot mutations as deletions and substitutions in the coding regions based on entropy greater than or equal to 0.3, leading to a total of 45 unique hotspot mutations. Moreover, 10286 Indian sequences are considered from 71038 global SARS-CoV-2 sequences as a demonstrative example which gives 52 unique hotspot mutations. Furthermore, the evolution of the hotspot mutations along with the mutations in variants of concern are visualised and their characteristics are discussed as well. Also, for all the non-synonymous substitutions (missense mutations), the functional consequences of amino acid changes in the respective protein structures are calculated using PolyPhen-2 and I-Mutant 2.0. In addition to this, SSIPe is used to report the binding affinity between the receptor binding domain of Spike protein and human ACE2 protein by considering L452R, T478K, E484Q and N501Y hotspot mutations in that region.